2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091338
|View full text |Cite
|
Sign up to set email alerts
|

In vivo polymerization of poly(3,4-ethylenedioxythiophene) (PEDOT) in rodent cerebral cortex

Abstract: Maintaining a reliable neural interface is a well-known challenge with implanted neural prostheses. Here we evaluate a method of forming an integrated neural interface through polymerization of PEDOT in vivo. Polymerization resulted in lower impedance and improved recording quality of local field potentials on implanted electrodes in the rat cerebral cortex. Histological analysis by optical microscopy confirmed successful integration of the PEDOT within tissue surrounding implanted electrodes. This technique o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…In spite of the promising results, little in vivo evidence has been presented to support the chronic stability and the benefit of applying CPs to neural interfacing electrodes. (Wilks et al, 2011) polymerized PEDOT in vivo within the rodent cerebral cortex, creating a direct CP interface with the neuronal tissue. In this work (Wilks et al, 2011) reported lowered impedance values, improved recording quality of local field potentials, and a tight cloud of PEDOT penetrating into the tissue surrounding the electrode.…”
Section: Coatings For Neural Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the promising results, little in vivo evidence has been presented to support the chronic stability and the benefit of applying CPs to neural interfacing electrodes. (Wilks et al, 2011) polymerized PEDOT in vivo within the rodent cerebral cortex, creating a direct CP interface with the neuronal tissue. In this work (Wilks et al, 2011) reported lowered impedance values, improved recording quality of local field potentials, and a tight cloud of PEDOT penetrating into the tissue surrounding the electrode.…”
Section: Coatings For Neural Interfacesmentioning
confidence: 99%
“…(Wilks et al, 2011) polymerized PEDOT in vivo within the rodent cerebral cortex, creating a direct CP interface with the neuronal tissue. In this work (Wilks et al, 2011) reported lowered impedance values, improved recording quality of local field potentials, and a tight cloud of PEDOT penetrating into the tissue surrounding the electrode. (Cui et al, 2003) were able to efficiently record neuronal activity for 2 weeks by implanting gold electrodes coated with PPy in guinea pigs cerebral cortex.…”
Section: Coatings For Neural Interfacesmentioning
confidence: 99%
“…[4][5][6][7] These conjugated polymeric materials can play an important role in bridging between neurons and electrodes due to their high electronic and ionic conductivity. Among the currently available conjugated polymers, poly (3,4-ethylenedioxythiophene) (PEDOT) has received considerable interest because of its low oxidation potential, relatively high chemical and thermal stability, and high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated the successful integration of PEDOT, lower impedance, and improved recording quality of local field potentials. 135 In other studies, both PEDOT and PPy nanotubes demonstrated better adherence to silicon dioxide surfaces, and demonstrated reduced impedance and increased charge capacity when compared to films made of the same materials. 136 Recent reports also discuss the fabrication of novel electrodes designed to help mitigate FBR and prolong chronic electrode function.…”
Section: Intracortical Neural Interface Recording Functionmentioning
confidence: 97%